2020
DOI: 10.1128/aac.00199-20
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2a Pharmacokinetic, Safety, and Exploratory Efficacy Evaluation of Oral Gepotidacin (GSK2140944) in Female Participants with Uncomplicated Urinary Tract Infection (Acute Uncomplicated Cystitis)

Abstract: Gepotidacin, a triazaacenaphthylene bacterial type II topoisomerase inhibitor, is in development for treatment of uncomplicated urinary tract infection (uUTI). This phase 2a study in female participants with uUTI evaluated the pharmacokinetics (primary objective), safety, and exploratory efficacy of gepotidacin. Eligible participants (n = 22) were confined to the clinic at baseline, received oral gepotidacin at 1,500 mg twice daily for 5 days (on-therapy period; days 1 to 5), and returned to the clinic for tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(69 citation statements)
references
References 20 publications
3
66
0
Order By: Relevance
“…Efficacy of gepotidacin was demonstrated in a phase 2 study in participants with uncomplicated urinary tract infection, in which the minimum gepotidacin urine concentrations remained above the clinically relevant gepotidacin minimum inhibitory concentration value of 4 μg/mL throughout the dosing interval. 8 Saliva concentrations displayed a linear relationship with plasma (both bound and unbound) gepotidacin concentrations (R 2 = 0.76). The ratio of saliva AUC to unbound plasma AUC was consistently close to unity (ratio of the AUC 0-t and AUC 0-∞ ranged from 0.746 to 0.839).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Efficacy of gepotidacin was demonstrated in a phase 2 study in participants with uncomplicated urinary tract infection, in which the minimum gepotidacin urine concentrations remained above the clinically relevant gepotidacin minimum inhibitory concentration value of 4 μg/mL throughout the dosing interval. 8 Saliva concentrations displayed a linear relationship with plasma (both bound and unbound) gepotidacin concentrations (R 2 = 0.76). The ratio of saliva AUC to unbound plasma AUC was consistently close to unity (ratio of the AUC 0-t and AUC 0-∞ ranged from 0.746 to 0.839).…”
Section: Discussionmentioning
confidence: 94%
“…In clinical trials, gepotidacin has demonstrated efficacy in acute bacterial skin and skin structure infections, uncomplicated urogenital gonorrhea, and uncomplicated urinary tract infection. [5][6][7][8] Gepotidacin is currently in phase 3 clinical studies for the treatment of uncomplicated urinary tract infection (1500 mg twice daily for 5 days) (ClinicalTrials.gov identification numbers NCT04020341 and NCT04187144) and uncomplicated urogenital gonorrhea (2 doses of 3000 mg separated by 10-12 hours) (ClinicalTrials.gov identification number NCT04010539).…”
mentioning
confidence: 99%
“…Gepotidacin is a novel, first-in-class triazaacenaphthylene antibiotic that inhibits bacterial DNA replication by a distinct mechanism of action ( 1 , 2 ), which confers activity against most strains of Escherichia coli , Staphylococcus saprophyticus , and Neisseria gonorrhoeae , including those resistant to current antibiotics ( 3 7 ). Phase 2 clinical trials indicated that gepotidacin may be a viable treatment for urogenital gonorrhea, uncomplicated urinary tract infection (UTI), and acute bacterial skin and skin structure infections ( 8 10 ). Phase 3 confirmatory studies are currently in progress to support urogenital gonorrhea (ClinicalTrials.gov identifier NCT04010539) and uncomplicated UTI (ClinicalTrials.gov identifiers NCT04020341 and NCT04187144) indications.…”
Section: Textmentioning
confidence: 99%
“…Throughout phase 1 and 2 clinical development, the pharmacokinetics (PK) of gepotidacin have been well defined in healthy adult participants ( 8 15 ) and in participants with renal or hepatic impairment ( 16 , 17 ). Gepotidacin formulations used in the PK evaluations included mesylate salt for an intravenous solution, capsules, tablets, and the free base for capsules and tablets.…”
Section: Textmentioning
confidence: 99%
“…Zoliflodacin is currently in a phase 3 clinical trial for uncomplicated gonorrhea [ 89 ]. Meanwhile, gepotidacin is being developed for uncomplicated UTI and uncomplicated gonorrhea [ 90 ].…”
Section: Current State Of Antimicrobial Drug Discoverymentioning
confidence: 99%